Potential Effects of the COVID-19 Pandemic on Future Birth Rate - Ullah, Md. Asad; Moin, Abu Tayab; Araf, Yusha; Bhuiyan, Atiqur Rahman; Griffiths, Mark D.; Gozal, David (Frontiers in Public Health, 2020)
Here, we examine the potential effect of the COVID-19 pandemic on future birth rates. This highly contagious disease originated in China, and rapidly spread worldwide, leading to extensive lockdown policies being implemented globally with the aim of containing the infection rates and its serious attendant consequences. Based on previous extant literature, this paper overviews the potential demographic consequences of the current progressively widespread epidemic on conception and fertility as driven by the data obtained during similar prior incidents. In general, epidemics manifest a common pattern as far as their impact on population, which is remarkably similar to natural disasters, i.e., a steep decline in birth rates followed by gradual increases and then followed by a baby boom. Additionally, we have also depicted how economic conditions, mental health, fear, and mortality may also influence future birth rates.